First Watch Franchise Expansion Proposal - Webb, Caitlyn; Knutson, Connor; Gamble, Tia (Kansas State University. K-State Libraries, 2017)
Our research team elected to analyze the profitability and marketability of expanding First Watch Daytime Café to Manhattan, Kansas, through market, competitive, and growth analyses. The market analysis utilizes primary data from a questionnaire and focus group to identify 1) the makeup of local consumer, 2) the demand present for Daytime Eatery restaurants and, 3) the common expectations shared by all consumers. The market analysis focuses on two primary factors: consumer feedback on the top three Daytime Eatery restaurants in Manhattan and consumer demand for the expansion of First Watch into the Flint Hills region. The competitor analysis implements a SWOT analysis to identify local competitor Strengths and Weaknesses and environmental Opportunities and Threats. The demand for consistent customer service is an example of an untapped opportunity that First Watch could leverage to achieve successful market entry. Additionally, increases in consumer demand and insufficient producer supply in the current Daytime Eatery market produce an inefficient market shortage. This shortage equates potential profit for First Watch, should they enter the market. The growth analysis is based on internal intelligence collected from interviews with managers of the top three local Daytime Eatery establishments. The managerial assessment is compiled into three sections: location, atmosphere, and customer service. Each of these areas bears significant impact on the presence of the restaurant in the Manhattan community. Through creating an efficient strategy based on the data and information collected in this report, the First Watch Leadership Team will be able to effectively diagnose the numerous environmental and company-specific factors that make investment in the Flint Hills regions profitable. The use and application of the three analyses in this report will enable First Watch Daytime Eatery to successfully enter and establish a strong competitive advantage in the Manhattan, Kansas, daytime eatery market.
Citation: Webb, C., Knutson, C., Gamble, T. (2017). First Watch Franchise Expansion Proposal. Unpublished manuscript, Kansas State University, Manhattan, KS.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: Daytime eatery; First Watch; Entrepreneurship; Business expansion; Economic development; Consumerism